Construction mediation in Scotland: An investigation into attitudes and experiences of mediation practitioners. Issue 2 (11th July 2016) - Trushell, Ian; Clark, Bryan; Agapiou, Andrew
Abstract : Purpose: This paper aims to address the knowledge gap, by exploring the attitudes and experiences of mediators relative to the process, based on research with practitioners in Scotland. Recent research on construction mediation in Scotland has focused exclusively on construction lawyers' and contractors' interaction with the process, without reference to the views of mediators themselves. Design/methodology/approach: The entire research design of this research was constrained by the small population of practising Scottish construction mediators (thought to be circa. 20 in 2013). The design encompassed a literature search, participant interviews, questionnaire survey and qualitative and quantitative data. The research questionnaire was designed to capture data related to the biography, training and experience of those interviewed before their opinion on the benefits of, and problems with, mediation were sought. Findings: The results indicate that mediations failed because of ignorance, intransigence and over-confidence of the parties. Barriers to greater use of mediation in construction disputes were identified as the lack of skilled, experienced mediators, the continued popularity of adjudication and both lawyer and party resistance. Notwithstanding the English experience, Scottish mediators gave little support for mandating disputants to mediate before proceeding with court action. A surprising number were willing to give an evaluation of the dispute rather than merely facilitating a settlement. Originality/value: There are few experienced construction mediators in Scotland, and the continued popularity of statutory adjudication is a significant barrier. Mediators believe that clients' negative perceptions of mediation are a bigger barrier than lawyers' perceptions. The mediators wanted judicial encouragement for mediation backed by some legislative support, mediation clauses incorporated into construction contracts and government adoption of mediation as the default process in its own contracts.